The contrarian effect : why it pays (big) to take typical sales advice and do the opposite - Port, Michael, 1970- (John Wiley & Sons, 2008)
Take the traditional sales model, which is outdated and needs a serious makeover, and turn it on its head by applying the advice in The Contrarian Effect: Why It Pays (Big) to Take Typical Sales Advice and Do the Opposite . Find an entirely sound approach to building better client relationships and closing more sales by doing the exact opposite that conventional sales advice dictates. Re-examine the most well-worn sales tactics in the business and discover specific and actionable strategies and principles that will help you close more sales today.